The application of Juliane House’s translation quality assessment model in the English translation of Yu Hua’s ‘Yanre de xiatian’ - Huan He; Mansour Amini; Malini Ganapathy; Salasiah Che Lah (Cogent Arts & Humanities)
The quality of some Chinese literary translations has raised concerns among some translation scholars. This qualitative study presents an examination of Juliane House’s latest translation quality assessment model in evaluating the quality of ‘Sweltering Summer’, the English translation of ‘Yanre de xiatian’, a short Chinese story. House’s model reveals that the translation quality is dependent on the matching degree of the textual profile and function between the original and translation. The article concludes that despite minor discrepancies along the dimensions of field, tenor, and mode leading to minor disagreements of ideational and interpersonal functional components between the source text and the target text, the original and its overt translation are largely equivalent at the level of language/text, register, as well as genre, and the overall quality of the translation remains adequate by providing mismatch and match examples and interpretations in support of the conclusion. This study confirms the feasibility and reliability of House’s model, offering insights for translation scholars interested in assessing translation quality in the realm of short literary works and providing constructive suggestions for translators of Chinese literature. Future research could explore sufficient syntactic and textual examples using quantitative data and the mismatches between the original and the translated texts.